2017
DOI: 10.1186/s12864-017-4003-0
|View full text |Cite
|
Sign up to set email alerts
|

Conclusive evidence for hexasomic inheritance in chrysanthemum based on analysis of a 183 k SNP array

Abstract: BackgroundCultivated chrysanthemum is an outcrossing hexaploid (2n = 6× = 54) with a disputed mode of inheritance. In this paper, we present a single nucleotide polymorphism (SNP) selection pipeline that was used to design an Affymetrix Axiom array with 183 k SNPs from RNA sequencing data (1). With this array, we genotyped four bi-parental populations (with sizes of 405, 53, 76 and 37 offspring plants respectively), and a cultivar panel of 63 genotypes. Further, we present a method for dosage scoring in hexapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 72 publications
1
48
0
Order By: Relevance
“…Lack of 1x0 markers on a homologue is possible if there is a high degree of inbreeding, the population is from a selfing, or if there is selection for a phenotype for which alleles have an additive effect. However, our experience in polyploid mapping to date has shown that low-dosage markers tend to be the most abundant marker type van Geest et al, 2017c). Nevertheless, we were not able to define one homologue on linkage group 4, even though all others each had 175 SNP markers or more.…”
Section: An Integrated and Phased Linkage Mapmentioning
confidence: 72%
See 4 more Smart Citations
“…Lack of 1x0 markers on a homologue is possible if there is a high degree of inbreeding, the population is from a selfing, or if there is selection for a phenotype for which alleles have an additive effect. However, our experience in polyploid mapping to date has shown that low-dosage markers tend to be the most abundant marker type van Geest et al, 2017c). Nevertheless, we were not able to define one homologue on linkage group 4, even though all others each had 175 SNP markers or more.…”
Section: An Integrated and Phased Linkage Mapmentioning
confidence: 72%
“…Dosage scoring from array output was mainly performed as described by (van Geest et al, 2017c). Because genomic dosage was highly correlated with the number of reads per allele from our sequence data (van Geest et al, 2017c), we estimated dosage per SNP of the parents a-priori based on the sequence data, and used this information for SNP calling.…”
Section: Genotyping and Marker Quality Filteringmentioning
confidence: 99%
See 3 more Smart Citations